The RNA-binding proteomes from yeast to man harbour conserved enigmRBPs - Beckmann, B; Horos, R; Fischer, B; Castello Palomares, A; Eichelbaum, K; Alleaume, A; Schwarz, T; Curk, T; Foehr, S; Huber, W; Krijgsveld, J; Hentze, M (Nature Publishing Group, 2015)
RNA-binding proteins (RBPs) exert a broad range of biological functions. To explore the scope of RBPs across eukaryotic evolution, we determined the in vivo RBP repertoire of the yeast Saccharomyces cerevisiae and identified 678 RBPs from yeast and additionally 729 RBPs from human hepatocytic HuH-7 cells. Combined analyses of these and recently published data sets define the core RBP repertoire conserved from yeast to man. Conserved RBPs harbour defined repetitive motifs within disordered regions, which display striking evolutionary expansion. Only 60% of yeast and 73% of the human RBPs have functions assigned to RNA biology or structural motifs known to convey RNA binding, and many intensively studied proteins surprisingly emerge as RBPs (termed ‘enigmRBPs’), including almost all glycolytic enzymes, pointing to emerging connections between gene regulation and metabolism. Analyses of the mitochondrial hydroxysteroid dehydrogenase (HSD17B10) uncover the RNA-binding specificity of an enigmRBP.